Analyzing the Sustainability of Micro, Small and Medium Enterprises during Covid-19 Pandemic in Bireuen Regency, Indonesia - Devi Andriyani; Fanny Nailufar; Yurina Yurina; Ratna Ratna; Mutia Rahmah (Research Collaboration Community (RCC), 2021)
This study aims to analyze the effect of product innovation, sales method, technology mastery, market share, and MSME compliance in muamalah on the sustainability of MSME food product during the Covid-19 pandemic in Bireuen Regency. The research method used multiple linear regression analysis method. Respondents in this study were 87 Micro, Small and Medium Enterprises (MSMEs) in food products. The results of the study partially found that the Product Innovation was the most dominant (significant) variable influencing the sustainability of MSMEs. The compliance in muamalah, reflected in sales zakat payment, honesty and transparency as well as product halalness, also had a significant effect on business sustainability. Meanwhile, the variables of sales method, technology mastery and market share expansion had no significant effect on business sustainability. Simultaneously, all independent variables had a significant effect on business sustainability and the ability to affect the independent variables on the dependent variable was 30.40%. The implication of this research is finding a solution to overcome the problem of the sustainability of MSMEs in Bireuen Regency. Whilst the limitation of the research is on collecting MSMEs data from the industry office, even though the conditions in the field are many Micro, Small and Medium Enterprises having not been registered and holding no a business license.